Determination of a free sound field to assess hearing aids. - Duran A., C.; Cornejo C., J.; Cadena M., M.; Granados T., P.; Longi P., A. (Revista Mexicana de Ingenieria Biomedica, 1989)
The behavior of a sound field for pure tones is illustrated with the use of three-dimensional graphics, where it is possible to appreciate its behavior for different frequencies. This also establishes its proximity to a free sound field in accordance with the rules of A.S.A. A sound meter fitted to a mobile support is used for this purpose.